Contributions of High Conservation Value Forests (HCVFs) on mammal diversity in heterogeneous oil palm landscapes - Abu-Bakar, Mohamad Azam Akmal; Mustafa, Naim; Mahmud, Hairulazim; Kasim, Ahmad Shahdan; Ramli, Zalifah; Afni, Sharifah Nur; Zainul Abidin, Kamaruddin; Abdul-Patah, Pazil; Azhar, Badrul; Zamzuri, Zamira Hasanah; Mohd-Taib, Farah Shafawati (Elsevier B.V., 2026)
Oil palm expansion has transformed lowland tropical forests across Southeast Asia, yet the landscape and accessibility features that sustain mammal diversity within plantation mosaics remain unclear. We quantified how topography and human access shape mammalian species richness and abundance in Peninsular Malaysia across three landscape types: monoculture oil palm (OPP), oil palm with forest patches (OPFP), and oil palm adjacent to contiguous forest (OPCF). We used Generalized Linear Mixed Models (GLMMs) to identify predictors of species richness and relative abundance (based on detection rates). Species richness increased with elevation and with distance from paved roads and showed a modest decline with increasing distance from unpaved service tracks. Abundance was highest in OPP and was strongly influenced by landscape type, increased with distance from paved roads, with a weaker positive association with elevation. Topography and road context jointly structure mammal communities in oil palm landscapes. Species richness was higher in elevated, less-accessible terrain, whereas high detection counts in monoculture plantations likely reflect the dominance of generalist species. State-scale actions such as buffering high-elevation forest, limiting new paved-road encroachment, and maintaining vegetated corridors along low-use service tracks may offer practical pathways to reconcile production with biodiversity goals.